Peripheral blood immune cell dynamics associate with growth of incidental indeterminate pulmonary nodules - Wang, Dongyuan; Hua, Lijuan; Bai, Wenxue; Guo, Mengyao; Lv, Yongman; Kuang, Dong; Guan, Hanxiong; Yu, Jun; Wang, Qi; Hao, Zhipeng; Sun, Wei; Zhang, Ni; et al. (Respiratory medicine, 2025)
Previous studies suggest peripheral blood immune cells associate with the progression and prognosis of lung cancer. The main purpose of this study was to explore the association of peripheral immune cell and its dynamics with the growth of pulmonary nodules. Of 9280 subjects whom had blood cell counts and chest CT scan in health check-up, 1068 participants were enrolled with the incidental pulmonary nodules of above 5 mm in diameter and subsequently followed up for 2 years. The pulmonary nodules were identified as growth based on the increase of at least 2 mm in the diameters within the two years. The relationships of pulmonary nodules growth with peripheral immune cell dynamics and clinical variables were analyzed using univariable inter-group comparison and multivariable logistic regression analyses. During the two years, 116 (10.9 %) of 1068 participants had the growth pulmonary nodules. Overall, emphysema, nodule diameter and non-solid characteristics associated with the growth of nodules. In the subgroup of pure solid nodules, high baseline eosinophil percentage (OR 1.220; 95 % CI 1.009–1.474; P = 0.040) and the increase of neutrophil count (OR 3.805; 95 % CI 1.027–14.093; P = 0.045) were significant risk factors for the nodule growth. In the subgroup of solid-predominant nodules, the increase of lymphocyte was associated with a lower risk of growth (OR 0.039; 95 % CI 0.002–0.839; P = 0.038). High baseline eosinophil and increase of neutrophil were associated with the growth of pure solid pulmonary nodules. The decrease of lymphocyte related to the growth of solid-predominant nodules. •Evaluated the associations between peripheral blood immune cell dynamics and the growth of incidental pulmonary nodules.•High baseline eosinophil and increase of neutrophil were associated with the growth of pure solid pulmonary nodules.3.The decrease of lymphocyte related to the growth of solid-predominant nodules.•The decrease of lymphocyte related to the growth of solid-predominant nodules.•Suggested the potential role of immune cells involved in the surveillance of early lung tumors.